Early resuscitation orders in hospitalized oldest-old with COVID-19: A multicenter cohort study. (July 2021) - Piers, Ruth; Van Braeckel, Eva; Benoit, Dominique; Van Den Noortgate, Nele
Background: In particular older people are at risk of mortality due to corona virus disease 2019 (COVID-19). Advance care planning is essential to assist patient autonomy and prevent non-beneficial medical interventions. Aim: To describe early (taken within 72 h after hospital admission) resuscitation orders in oldest-old hospitalized with COVID-19. Setting/participants: A cohort of patients aged 80 years and older admitted to the acute hospital in March and April 2020 with COVID-19 were retrospectively recruited from 10 acute hospitals in Belgium. Recruitment was done through a network of geriatricians. Results: Overall, 766 octogenarians were admitted of whom 49 were excluded because no therapeutic relationship with the geriatrician and six because of incomplete case report form. Early decisions not to consider intensive care admission were taken in 474/711 (66.7%) patients. This subgroup was characterized by significantly higher age, higher number of comorbidities and higher frailty level. There was a significant association between the degree of the treatment limitation and the degree of premorbid frailty ( p < 0.001). Overall in-hospital mortality was 41.6% in patients with an early decision not to consider intensive care admission (67.1% in persons who developed respiratory failure vs 16.7% in patients without respiratory failure ( p < 0.001)). Of 104 patients without early decision not to consider intensive care admission but who developed respiratory failure, 59 were eventually not transferred to intensive care unit with in-hospital mortality of 25.4%; 45 were transferred to the intensive care unit with mortality of 64.4%. Conclusions: Geriatricians applied all levels of treatment in oldest-old hospitalized with COVID-19. Early decisions not to consider intensive care admission were taken in two thirds of the cohort of whom more than 50% survived to hospital discharge by means of conservative treatment.